A Comparative Genre-Based Error Analysis of EFL Students’ Academic Paragraphs Written in a Timed Examination - Marliana, Elli; Jazadi, Iwan (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
Writing is widely regarded as one of the most challenging skills for learners of English as a Foreign Language (EFL), particularly in academic contexts, where students are required to produce coherent, linguistically accurate texts. This study investigates the types and frequencies of writing errors produced by EFL students across three academic paragraph genres: descriptive, comparison–contrast, and cause–effect. Adopting a qualitative descriptive design with an error-analysis approach, the study analyzed academic paragraphs written by 24 undergraduate students during a time-controlled final examination in a paragraph-writing course. Students’ writing errors were identified, categorized into grammatical, lexical, mechanical, and organizational errors, and compared across paragraph genres. The findings reveal that grammatical errors were the most prevalent across all genres, whereas mechanical and organizational errors varied by genre. Descriptive paragraphs exhibited high frequencies of grammatical and mechanical errors, comparison–contrast paragraphs showed prominent organizational difficulties, and cause–effect paragraphs demonstrated fewer errors overall but persistent grammatical challenges. These results demonstrate clear cross-genre differences in error patterns, indicating that paragraph genre significantly influences students’ writing difficulties. The study contributes to EFL writing research by highlighting the genre-sensitive nature of writing errors and underscores the need for genre-based instruction, feedback, and assessment in EFL paragraph writing pedagogy.